Kesuburan Tanah dan Produktivitas Padi pada Budidaya Organik, Semi Organik, dan Konvensional di Kabupaten Sragen - Sukristiyonubowo Sukristiyonubowo; Damas Riyanto; Sugeng Widodo (Agrotechnology Research Journal, 2019)
The farmers realize that Green Revolution technology with external inputs (mineral fertilizer and pesticide) is no longer sustainable and cost production become too expensive. The farmers want to move to organic, semi organic and some remain doing conventional farming system. The aim of the research was to study the dynamic of soil fertilities and biomass production under organic, semi organic and conventional rice farming systems. The study was conducted in Termes Village Sambung Macan Sub District, Sragen District, Central Java and Analytical Laboratory of the Yogyakarta Assessment Institute for Agricultural Technology from March 2017 to 2018. Soil composites were taken in March 2017 and in 2018 at organic, semi organic and conventional rice farming systems. The results showed that in general the soil chemical fertility taken in 2018 under three rice farming were better than soil sampled in 2017 including pH, C organic, N total, P and K extracted with HCl 25 %. The same results were happened in rice biomass production, in organic rice farming was more excellent compared to semi organic and conventional rice farming and in semi organic was better than conventional rice farming because of soil C-organic content were higher.